Prevalence Of Technology Induced Stress Among Medical Students - S, Susithra.; T, Murugaraj.; Elayaperumal, Shanmugananth; A, Tharifa.; S, Shapna. (Journal of Neonatal Surgery, 2025)
Background: Technology induced Stress (TIS) occurs when the technology develops beyond the human knowledge. Students finds difficulty in using advanced digital gadgets for improving their studies and knowledge due to fast growing technology, students undergone technology induced stress. Understanding the prevalence of technology induced stress among medical students is essential for providing treatment for this syndrome and with increasing prevalence among medical students, Awareness and research into this syndrome are vital for improving the student health and performance in carrier. Its prevalence of (TIS) in Puducherry is yet to be established. In order to understand the prevalence of technology induced stress among medical students the study is conducted. Aim: To identify the prevalence of technology induced stress among medical students. Methods: It is a cross-sectional study observation study population will be assessed with technostress creator’s questionnaire and the data’s will be recorded. Result: totally 100 participants were participated in this study in which study found that Techno-Uncertainty (χ² = 10.87, p = 0.003, 62%) and Techno-Overload (χ² = 14.32, p = 0.001, 60%) were the most significant contributors to technostress among medical students. Additionally, female students (χ² = 12.45, p = 0.002, 58%) and older students (χ² = 10.87, p = 0.003, 55%) reported higher stress levels, emphasizing the need for institutional support. Conclusion: The study showed that medical students are more probably to experience technology-induced stress.